Integrating Gender Equality into Business and Management Education : Lessons Learned and Challenges Remaining - Flynn, Patricia M. (Taylor and Francis, 2017)
"This volume addresses the need to integrate gender equality into business and management education and provides examples of leadingÂ initiatives illustrating how this can occur from various disciplinary and global perspectives. Â Gender inequality has a long history in business schools and the workplace, and traditions are hard to change. Some disciplines remain resolutely gendered, affecting both women and men; and case materials on women leaders and managers are still rare. The chapters provide conceptual and research rationales as to why responsible management education must address the issue of gender equality. They also identifyÂ materials and resources to assist faculty in integrating gender issues and awareness into various disciplines and fields. These include specific case studies and innovations that assess or address the role of gender in various educational environments. The book is designed to help faculty integrate the topic of gender equality into their own teaching and research and gain support for the legitimacy of gender equality as an essential management education topic. This is the first book in a series on gender equality as a challenge for business and management education, published with the Principles of Responsible Management Education (PRME)Â Working Group on Gender Equality."- Resumé vydavatel
Keywords: sexuální diskriminace; diskriminace žen; diskriminace v zaměstnání; manažerské vzdělávání; sex discrimination; discrimination against women; discrimination in employment; managerial education; elektronické knihy; sborníky; electronic books; papers of several authors